Marital Rape di Kampung Nelayan: Pandangan Sosiologis - Ghony, M. Djunaidi (ULUL ALBAB Jurnal Studi Islam, 2004)
This research of marital rape at fisherman community on Sendangbiru. By using the sociological paradigm and of the case approach and the descriptivequalitative analysis, this research find out that: (1) There are marital rape realities in fishennan community environment; (2) Some factors that pushing the marital rape are: so ciological, a n thropological and psychological factors that sustained by understanding of nonnative and textual of religion doctrine; (3) the Marrital rape can be enforcing rapist, physical and psychical victim, and prostitution rape, that is woman become" social-prostitute". By the orhertype the caracrerlstic of marrital r ape can be defined as: anger rape, exploitation rape, and humanity crime or sadistic rape; (4) The fisherman community view that this reality showing the stereo typing socialize and the social tradition influenced by textualist'dogma of religion, namely the woman considered to be "steward" and "subordination" of men (the husband); and (5) Meanwhile, the majority of woman is over a barrel in answering the problems, so that they look this facts as factual reality, as what religion (Cristien and Islam) desire. Partly among the woman try to solve the problems through the law, but they just remain to be find "the justice" in gender deflected.